The role of the Dermatology Nurse Practitioner in the Western Cape as perceived by nurses and other health care practitioners - Ndyenga, Nomgcobo Anthia (Division of Nursing and Midwifery, 2022)
Background information Most dermatologists in South Africa practice in urban areas whereas rural populations have limited access to dermatology services. The first group of dermatology nurses in South Africa was trained in 1997, through a short course programme offered at Groote Schuur Hospital in Cape Town, to increase access to care. These nurses provide dermatological treatment and care in a variety of health care settings; however, their role has not been formally described. Aim of the Study The study aim was to explore and describe the role of a dermatology nurse practitioner at primary and tertiary care in the Western Cape Province, South Africa, as perceived by dermatologists, physicians, dermatology nurse practitioners, non-dermatology trained nurses and nurse managers who have worked with dermatology nurses. Methodology A qualitative, descriptive and exploratory design was selected for the study. Purposive sampling was used to select participants who were doctors and nurses and who had been involved in rendering dermatological services. Participants were drawn from public and private health care institutions at primary and tertiary care levels. Individual interviews, using a semi structured interview schedule, were conducted with three nurses, two medical officers, three nurse managers and four dermatologists. A focus group was conducted with seven dermatology nurse practitioners. Data were analysed using content analysis. Findings The findings show that dermatology nurse practitioners are not only involved in clinical care of patients, but have other roles which include education, management of the services and leadership. The benefits of dermatology nurse practitioners' roles for the patient include increased access to care, improved quality of life and reduced costs. The health system is thought to have benefitted from reduced referrals to tertiary care as more patients are effectively managed at primary care level. Challenges to the role include a lack of support for the dermatology nurse practitioners, inadequate resources and lack of regulation. Recommendations include a call for accreditation of dermatology nursing and provision of learning opportunities for DNPs. The findings of the study may not reflect the experiences and perceptions of practitioners beyond this region as the study was limited to the Western Cape. Conclusion The value of the dermatology nurse practitioners has been appreciated by all stakeholders in this study. If recognised by statutory bodies and the role of the dermatology nurse practitioner is regulated, it has the potential to expand the reach of dermatology services and contribute to the overall health care for persons with skin disorders.